(3MRH GdbQGAI ddENhGf hGdNdGfs
(3ChdgG (B:s
(3HOCJ HMeO Gddg aj GdPcQ ChdkG hCQOaJ TcQkG KGfjkG oeJaVdkG gPg oLed aj aVd GdbQBf GdeLjO JfRjd ef Mcje MejO s
(3BNQgG (B:s
(3JeJ HYhf Gddg fXekG bUjOJj hHYO MeOJ Gddg bhdkG heaYdG hCHjGJgG SHYhf eYg KdGKI HSJeGFI bUQkG hdjS eWhdG s
(3GdfSNI HgG MhGTs
(3fSNJ ef fSNI JGQjNgG (B1181 (3g` HNW YHOGdbGOQ GdMfajs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdbQGAGJ hGdJLhjOs